Acute correction of electromechanical dyssynchrony and response to cardiac resynchronization therapy - Ghassan Moubarak; Guillaume Viart; Frédéric Anselme (ESC Heart Failure)
Abstract Aims Echocardiographic measures of dyssynchrony at baseline have not demonstrated a good ability to predict response to cardiac resynchronization therapy (CRT). The purpose of this study was to determine if the acute correction of electromechanical dyssynchrony, assessed by the change in simple pulsed‐Doppler measures, was related to CRT response at 6 months. Methods and results Echocardiography was performed at baseline and at pre‐discharge after CRT implantation. Intraventricular, interventricular, and atrioventricular dyssynchrony were evaluated by the left pre‐ejection interval (LPEI), the interventricular mechanical delay, and the ratio of left ventricular filling time to RR interval, respectivelxy. A patient was considered responder if he/she was alive without hospitalization for heart failure and had an absolute increase of left ventricular ejection fraction (LVEF) >5 points. Forty‐eight patients (mean age 67 ± 11 years, 73% male, mean LVEF 30 ± 5%) were included. CRT led to an acute correction of intraventricular and interventricular dyssynchrony but not to an acute correction of atrioventricular dyssynchrony. There were 31 (65%) responders at 6 months. Two factors were independently associated with CRT response in multivariate analysis: ischemic cardiomyopathy (odds ratio 0.19, 95% confidence interval 0.04–0.87; P= 0.032) and delta LPEI (odds ratio 1.03 per 1 ms decrease, 95% confidence interval 1.01–1.05; P = 0.007). By receiver operating characteristic analysis, the optimal cut‐off value of delta LPEI was −16 ms. The proportion of responders in patients without ischemic cardiomyopathy and with a delta LPEI greater than −16 ms was 85%. Conclusions Acute correction of intraventricular electromechanical dyssynchrony evaluated by the LPEI predicted CRT response at 6 months.